Robust JPEG/JPEG-2000 image transmission with error resilient coding - Nyi Min Aung (2008)
An error resilient coding scheme for JPEG image transmission based on data embedding and side-match vector quantization (VQ) is implemented to recover high quality JPEG images from the corresponding corrupted images.